Suitability of Tartrate-Resistant Acid Phosphatase Type 5b as a Screening Marker for Bone Mineral Density in Community-Dwelling Elderly Individuals - Irie, Sumiko; Hayashida, Naomi; Shinkawa, Tetsuko; Taira, Yasuyuki; Sekitani, Yui; Teraoka, Seitaro; Hashiguchi, Kanami; Yoshida, Koji; Morishita, Michiko; Takamura, Noboru (The Tohoku Journal of Experimental Medicine, 2011)
Osteoporosis is a common disorder in aging populations that imposes considerable health problems. Tartrate-resistant acid phosphatase type 5b (TRAP-5b) is derived from osteoclasts, and is involved in normal bone homeostasis. Recently, a novel assay system for TRAP-5b, the fragments absorbed immunocapture enzymatic assay method, has been developed. To evaluate the suitability of TRAP-5b as a screening marker for bone mineral density (BMD), we explored the correlations between serum TRAP-5b concentrations and laboratory findings, body mass index, or BMD in 462 community-dwelling elderly individuals (249 men and 213 women, age 73.4 ± 6.5 years) who participated in a regular medical screening program. By multivariate linear regression analysis adjusted for confounding factors, TRAP-5b was significantly correlated with body mass index (β = −0.005, p = 0.043), alkaline phosphatase, a marker for osteoid formation and calcification (β = 0.001, p < 0.001), and triglyceride (β = −0.097, p = 0.016) in men, and with body mass index (β = −0.009, p = 0.025), alkaline phosphatase (β = 0.001, p < 0.001), calcium (β = −0.059, p = 0.039), and bone trabecular area ratio (β = −0.47, p = 0.025) in women. In conclusion, the elevated serum level of TRAP-5b is independently correlated with the decreased BMD in women, but not in men. Because measurement of TRAP-5b is not affected by food intake, and blood samples can be collected at any time of the day, we suggest the suitability of serum TRAP-5b as a simple marker for the evaluation of BMD in women.